EFFECT OF GRAIN MOISTURE OF CORN AT HARVESTING ON SOME AGRONOMIC TRAITS - & Alkazaali, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted during spring and fall seasons, 2015 , at the fields of Field Crop Department – College of Agriculture –University of Baghdad . The objective was to study the effect of grain moisture at harvesting on some agronomic traits of the corn next generation , by using synthetic variety 5018 . In spring season 2015 , seeds of this variety was planted ,when moisture of the ear grains was (37-42%) , ten ears were harvested. Ear harvesting dates were performed manually when the grains had 37-42% , 34-36% , 30-33% , 25- 28% and 19-22% moisture content. In fall season 2015 , varietal trail was carried out to the five treatment materials , using Randomized Complete Bock Design , with four replicates. The results revealed , that non significant differences between treatments (19-22)% and (25-28)% , in all the studied traits . The plants grown from the seeds of (25-28)%, were produced highest vegetative mass (116.30 g.plant-1) , total dray matter (269 g. plant-1) and total dray matter ( 1.80 kg.m-2 ) . Highest grain yield ( 1.07 kg.m-2 ) and harvesting index ( 0.63) were produced from plants grown from seeds harvested with (19-22)% moisture content . It can be concluded that the best moisture contents of the grains for seed production was (19-28)%.